Family Quality of Life as A Determinant of The Environmental Attitude in Muslim Students - Hasbullah, Hasbullah; Raudatussalamah, Raudatussalamah; Mukhlis, Mukhlis; Jannah, Putri Miftahul; Salmiyati, Salmiyati (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
AbstractEnvironmental Attitude is a positive or caring attitude that influences individual behavior to engage in activities related to the surrounding environment. Family Quality of Life (FQOL) is one of the main factors that influence students to have a caring attitude toward their environment, especially at school. This research aims to examine the role of family quality of life (FQOL) on environmental awareness (environmental attitude) among high school students in Riau Province. The subjects in this research were 734 students from 5 high schools who lived with their parents in Riau Province. The selection of schools in this research was carried out using non-probability sampling techniques based on accidental sampling. The data collection technique in this research was carried out by administering an environmental attitude and Family Quality of Life (FQOL) scale. Data analysis in this research was carried out using multiple regression techniques. Based on the results of the analysis that has been carried out, it shows a significant influence between the Family Quality of Life (FQOL) variable on Environmental Attitude. This means that the quality of family life for students can greatly influence their attitude of caring for the environment, especially at school.Â Environmental Attitude merupakan sikap positif atau kepedulian yang mempengaruhi perilaku inidividu untuk terlibat dalam aktivitas yang berkaitan dengan lingkungan sekitarnya. Kualitas kehidupan dalam keluarga atau Family Quality of Life (FQOL) menjadi salah satu faktor utama yang dapat mempengaruhi siswa memiliki sikap peduli terhadap lingkungannya terutama di sekolah. Penelitian ini bertujuan untuk mengkaji peran kualitas hidup keluarga (FQOL) terhadap kepedulian lingkungan (environmental attitude) pada siswa SLTA di Provinsi Riau. Subjek dalam penelitian ini sebanyak 734 siswa dari 5 SLTA yang tinggal bersama orangtua di Provinsi Riau. Pemilihan sekolah dalam penelitian ini dilakukan dengan menggunakan teknik random sampling dan pengambilan sampel dilakukan dengan menggunakan teknik non probability sampling berdasarkan aksidental sampling. Teknik pengumpulan data dalam penelitian ini dilakukan dengan mengadministrasikan instrumen penelitian skala environmental attitude dan Family Quality of Life (FQOL). Analisis data dalam penelitian ini dilakukan dengan menggunakan teknik regresi berganda. Berdasarkan hasil analisis yang telah dilakukan menunjukkan hasil bahwa terdapat pengaruh yang signifikan antara variabel Family Quality of Life (FQOL) terhadap Environmental Attitude. Artinya bahwa kualitas dalam kehidupan keluarga bagi siswa dapat memberikan pengaruh besar terhadap sikap kepeduliannya dengan lingkungan terutama di sekolah.